Water flow patterns and pesticide fluxes in an upland soil in northern Thailand - H. Ciglasch (2018)
Rapid percolation of water through soil facilitates both the recharge and the contamination of ground-water reservoirs. We have studied the variation of water flux and pesticide leaching through a soil in northern Thailand. At a depth of 55cm, two pits were equipped with tensiometer-controlled glass suction lysimeters that were connected to a novel on-line solid-phase extraction device. Nine insecticides varying in water solubility from 10-2 to 10 +6 mg-1 were applied on the soil surface, and leaching was monitored for 8 weeks. Measured water fluxes were compared with simulated values. Total recovery ranged from traces (malathion, triazophos) to 1.3% (dimethoate) of the applied amount, showing a decreasing retardation with increasing polarity of the substances. All pesticides were detectable in the soil solution during the first rain after application. Due to fingering, 83% of the leachate was transported through 38% of the area at leaching rates of < 2mm per day. A new adaptation of the Simpson Index revealed that the diversity of the flow pattern increased exponentially with decreasing rates of seepage water flux (R2 = 0.80). No such correlation was found when leaching was faster, indicating that the flow pattern switched from a fingering- to a matric-dominated flux. No long-term leaching of insecticides was observed. The two profiles studied behaved similarly in terms of both water and pesticide transport. Therefore we suggest that the flow pattern is a stable property of the soil that can be accurately described by our combination of novel experimental setup and statistical analysis of the flow field. © 2005 British Society of Soil Science.